2015
DOI: 10.1039/c5ra17223c
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transition in hydrogen-bonded molecular crystal acetamide: combined Raman scattering and X-ray diffraction study

Abstract: The structural and vibrational properties of acetamide under high pressure were probed by in-situ synchrotron X-ray diffraction (XRD) and Raman scattering up to ~ 10 GPa. Two structural phase transitions are observed at 0.9 and 3.2 GPa, evidenced by the obvious changes in Raman spectra as well as the discontinuities of peak positions versus pressure. The phase transitions are further confirmed by the significant changes of XRD patterns. The two phase transitions are proposed to originate from the rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In this way, one can use the presence of splittings in the vibrational Raman spectra of TFMBI single crystals to assess for the onset of the phase transition. Despite this simple principle, we expect practically only those modes whose atomic motions affect the symmetry of a given dimer pair of TFMBI molecules will split, and these splittings will not occur for all the normal modes of the high-temperature phase, as we find below. , …”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In this way, one can use the presence of splittings in the vibrational Raman spectra of TFMBI single crystals to assess for the onset of the phase transition. Despite this simple principle, we expect practically only those modes whose atomic motions affect the symmetry of a given dimer pair of TFMBI molecules will split, and these splittings will not occur for all the normal modes of the high-temperature phase, as we find below. , …”
Section: Resultsmentioning
confidence: 78%
“…Despite this simple principle, we expect practically only those modes whose atomic motions affect the symmetry of a given dimer pair of TFMBI molecules will split, and these splittings will not occur for all the normal modes of the high-temperature phase, as we find below. 51,52 Measured and Computed Raman Spectra. We break down our presentation of the experimental and computed Raman spectra of TFMBI into five parts associated with separate spectral regions.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Bennett et al have demonstrated the crystal–amorphous reversible phase transitions in a zeolitic imidazolate framework at pressure compression and decompression stages . Zou and his team have performed the static-high-pressure experiment and reported the reversible crystallographic phase transition for ammonium formate, lithium amide, acetamide, and magnesium silicide (Mg 2 Si) …”
Section: Introductionmentioning
confidence: 99%
“…9 Bennett et al have demonstrated the crystal− amorphous reversible phase transitions in a zeolitic imidazolate framework at pressure compression and decompression stages. 10 Zou and his team have performed the static-highpressure experiment and reported the reversible crystallographic phase transition for ammonium formate, 11 lithium amide, 12 acetamide, 13 and magnesium silicide (Mg 2 Si). 14 Followed by the analysis of static-high-pressure and hightemperature observations, dynamic shock wave-induced phase transition experiments conducted on solids can also provide significant information that helps researchers understand the behaviors of molecules and atoms and their response at dynamic-high-transient-pressure and temperature conditions, which have been identified to be one of the rising research topics in recent years.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[10][11][12][13] Moreover, it could be noted that so far several research articles have been published based on the shock-wave-induced phase transitions whereas the reversible phase transition of materials enforced by shock waves is not yet well understood. In contrast, it is quite common to find materials at hydrostatic pressure compression and de-compression conditions which are well documented as exhibited by several materials such as acitamide, [14] lithium amide, [15] ammonium formate, [16] and magnesium silicide. [17] Reversible phase change (from amorphous to crystalline) materials are always given prime importance as they have a wide array of technological applications such as switchable dielectrics, thermal energy storage devices, piezoelectrics, ferroelectrics, pyroelectric as well as nonlinear optical channel waveguides as compared to the phase changing materials of forward or backward phase transitions.…”
mentioning
confidence: 99%